Brain connectivity abnormalities extend beyond the sensorimotor network in peripheral neuropathy. Issue 2 (25th October 2012) - Rocca, Maria A.; Valsasina, Paola; Fazio, Raffaella; Previtali, Stefano C.; Messina, Roberta; Falini, Andrea; Comi, Giancarlo; Filippi, Massimo
<x xml:space="preserve">Abstract</x> Objectives: To investigate, using resting state (RS) functional connectivity (FC), the selectivity of involvement of the sensorimotor network in patients with acquired (A) and with hereditary (H) peripheral neuropathies (PN) and the correlations of RS FC abnormalities with clinical impairment and structural brain damage. Temporal associations among RS networks were also explored. Experimental design: RS fMRI scans were acquired from 13 APN, 12 HPN, and 18 age‐ and sex‐matched healthy controls. Independent component analysis and functional network connectivity were used to investigate RS FC within and among RS networks with potential functional relevance. Principal observations: Compared to controls, patients had a decreased FC of the right precentral gyrus and an increased RS FC of the precuneus within the sensorimotor network. Both decreased and increased RS FC also involved the visual and auditory networks, which additionally had an increased coherence of function with the sensorimotor network (more pronounced in HPN). RS FC modifications in patients extended to several cognitive networks and were correlated with disease duration. In APN, they were also correlated with the severity of clinical impairment and corpus callosum atrophy. Conclusions: In PN, RS FC modifications extend beyond the sensorimotor network and involve other sensory and cognitive networks. The correlations between RS FC patterns and disease duration in patients as well as with clinical impairment in patients with APN suggest that modifications of FC might reflect an adaptive mechanism, which takes time to occur and helps to limit the clinical consequences of peripheral damage. Hum Brain Mapp 35:513–526, 2014. © 2012 Wiley Periodicals, Inc.